PERSEPSI DAN PENGETAHUAN GENERASI MILLENIAL TERHADAP PRODUK HALAL - Agus Mahardiyanto; Moehammad Fathorrazi; Suparman; Zainuri; Agus Priyono (Bajang Institute, 2022)
Besuki Raya is a former residency in East Java in the East. This area is an area with a strong traditional Islamic tradition. However, research is still rare that explores their perceptions and knowledge, especially the Millennial generation of halal products. This research tries to explore the perceptions and knowledge of the Millennial generation of halal products in the Besuki Raya area. The research method used quantitative with an explanatory approach, primary data in the form of purposive sampling as many as 108 respondents were collected from the Besuki Raya millennial generation in various agencies. The research analysis test used Multiple Linear Regression Analysis. The results of the Data Analyst Test show that the Millennial generation in Besuki Raya have good knowledge of halal products. They understand about halal certification, Halal labeling and knowledge about halal products that are consumed even though the level of religiosity is different. There is a negative analysis result related to perception, this low perception is influenced by the dualism of religious elites in understanding sharia compient products..